A Modified Vancomycin Molecule Confers Potent Inhibitory Efficacy against Resistant Bacteria Mediated by Metallo-β-Lactamases - Le Zhai; Ya Liu; Yue Jiang; Ling-Yan Kong; Jian Xiao; Yi-Xue Wang; Yang Shi; Yi-Lin Zhang; Ke-Wu Yang (Molecules, 2022)
Multidrug-resistant bacterial infections mediated by metallo-β-lactamases (MβLs) have grown into an emergent health threat, and development of novel antimicrobials is an ideal strategy to combat the infections. Herein, a novel vancomycin derivative Vb was constructed by conjugation of triazolylthioacetamide and vancomycin molecules, characterized by reverse-phase high performance liquid chromatography (HPLC) and confirmed by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS). The biological assays revealed that Vb effectively inhibited S. aureus and methicillin-resistant S. aureus (MRSA), gradually increased the antimicrobial effect of β-lactam antibiotics (cefazolin, meropenem and penicillin G) and exhibited a dose-dependent synergistic antibacterial effect against eight resistant strains tested, which was confirmed by the time-kill curves determination. Most importantly, Vb increased the antimicrobial effect of meropenem against the clinical isolates EC08 and EC10 and E. coli producing ImiS and CcrA, resulting in a 4- and 8-fold reduction in MIC values, respectively, at a dose up to 32 μg/mL. This work offers a promising scaffold for the development of MβLs inhibitors, specifically antimicrobials for clinically drug-resistant isolates.